BS EN IEC 60115-4-10. Fixed resistors for use in electronic equipment. Part 4-10. Blank detail specification. Power resistors with axial leads for through-hole assembly on circuit boards (THT), for general electronic equipment. Classification level G (21st March 2023) - British Standards Institution,
No abstract available